Iron‐nickel hydroxide nanoflake arrays supported on nickel foam with dramatic catalytic properties for the evolution of oxygen at high current densities. (23rd June 2020) - Hu, Hua‐Shuai; Si, Si; Liu, Rui‐Jie; Wang, Chong‐Bin; Feng, Yuan‐Yuan
Summary: Ultrathin FeNiOx Hy nanoflake arrays with the thickness of only 4.5 nm were prepared on Ni foam (NF) via a facile hydrothermal reaction. The oxygen evolution reaction (OER) properties of the obtained sample (FeNiOx Hy /NF) were investigated under alkaline conditions (1.0 M KOH). The optimized FeNiOx Hy /NF displays extremely small overpotentials of only 195 and 306 mV to achieve the current densities of 10 and 1000 mA cm −2, respectively, and shows almost no potential attenuation during the 160 hours of stability test even the current density is up to 1000 mA cm −2, demonstrating brilliant OER catalytic activity and durability. FeOOH and the NiOOH produced from the in situ oxidation of the surface Ni atoms of the NF substrate are the active sites. The synergistic effect between FeOOH and NiOOH is responsible for the high performances. To our knowledge, the high activity and stability of FeNiOx Hy /NF catalyst outperform almost all of the OER catalysts reported to date. These informative findings are valuable not only for understanding the mechanism of OER but also for the design of cheap transition metal catalysts for industrial water electrolysis at high current densities. Abstract : Iron‐nickel hydroxide nanoflake arrays with excellent performances for oxygen evolution reaction at high current densities.